2016
DOI: 10.1186/s12936-016-1551-8
|View full text |Cite
|
Sign up to set email alerts
|

Communication for behavioural impact in enhancing utilization of insecticide-treated bed nets among mothers of under-five children in rural North Sudan: an experimental study

Abstract: BackgroundMalaria is the leading cause of morbidity and mortality in Sudan. The entire population is at risk of contracting malaria to different levels. This study aimed to assess the effectiveness of communication for behavioural impact (COMBI) strategy in enhancing the utilization of long-lasting insecticidal nets (LLINs) among mothers of under-five children in rural areas.MethodsA randomized community trial was conducted in rural area of Kosti locality, White Nile State, Sudan, among mothers of under-five c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
8

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 21 publications
0
16
8
Order By: Relevance
“…Although a limited number of studies explore ITN use among children in relation to caregiver exposure to relevant SBC messages, more studies look at ITN use among other household members in relation to exposure to SBC messages. In other parts of sub-Saharan Africa, studies show that SBC exposure has positive effects on ITN use in a variety of populations, including women of reproductive age [10], mothers of children under five [15], and all household members [14, 18]. Moreover, two studies conducted in Nigeria show that SBC exposure had positive effects on ITN use among household heads and their spouses [6] and all household members [5].…”
Section: Discussionmentioning
confidence: 99%
“…Although a limited number of studies explore ITN use among children in relation to caregiver exposure to relevant SBC messages, more studies look at ITN use among other household members in relation to exposure to SBC messages. In other parts of sub-Saharan Africa, studies show that SBC exposure has positive effects on ITN use in a variety of populations, including women of reproductive age [10], mothers of children under five [15], and all household members [14, 18]. Moreover, two studies conducted in Nigeria show that SBC exposure had positive effects on ITN use among household heads and their spouses [6] and all household members [5].…”
Section: Discussionmentioning
confidence: 99%
“…Several approaches, such as Information Education and Communication (IEC), Communication-for- Behavioural- Impact (COMBI), Behaviour Change Communication (BCC) and school-based health education, have been suggested and implemented to promote uptake of malaria interventions [ 8 12 ]. These approaches are aimed at enabling people to improve their health, access appropriate treatment, and adopt preventive measures.…”
Section: Introductionmentioning
confidence: 99%
“…A study in Ogun State, Nigeria recorded an increase in insecticidal nets utilization from 29.5% to 72.6%, another study in Jos, Nigeria recorded an increase from 4.6% to 88.4%, other studies found an increase of 28.8% to 89.6% and19.2% to 82.2% in Enugu, Nigeria and Sudan respectively. Findings in intervention communities were statistically significant compared with the [23][24][25][26] control communities.…”
Section: Ethical Considerationmentioning
confidence: 87%